A facile approach towards fabrication of lightweight biodegradable poly (butylene succinate)/carbon fiber composite foams with high electrical conductivity and strength. (3rd May 2018) - Kuang, Tairong; Ju, Jiajun; Yang, Zheyu; Geng, Lihong; Peng, Xiangfang
Abstract: Lightweight electrically conductive biodegradable polymer composites have been considered as a promising environmental-friendly alternative to replace the traditional petroleum-based CPCs because of the economic and ecological drawbacks of petroleum-based plastics. Herein, we demonstrated a facile and effective way to fabricate poly (butylene succinate) (PBS)/carbon fiber (CF) composites foams with lightweight, high-strength and improved conductive networks through the combination of solvent mixing, micro-injection molding and supercritical carbon dioxide (Sc-CO2 ) foaming methods. Results showed that the resulting composite foams possessed much higher electrical conductivity (the percolation threshold decreased from 3.6 to 7.4 to 1.04–2.37 vol%), suggesting that the introduction of foaming technique could be beneficial for the formation of effective 3D conductivity networks. The composite foams presented a good compressive strength and a low density (reduced around ∼50%). Moreover, effects of different length and content of CF on the mechanical and thermal performance, rheological behavior, foaming properties and electrical conductivities of PBS/CF composites have been investigated.